2021
DOI: 10.1089/pmr.2021.0004
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Its Relationship with Pain in Patients with Advanced Cancer Cachexia: Secondary Cross-Sectional Analysis of a Multicenter Prospective Cohort Study

Abstract: Background: Limited information is available on the relationship between C-reactive protein (CRP) levels and pain in advanced cancer. Objectives: To investigate the relationship between serum levels of CRP and subtypes of pain. Design: A secondary cross-sectional analysis of a prospective cohort study. Setting/Subjects: Patients with advanced cancer admitted to 23 palliative care units in Japan. Measurements: Patients rated the severity of pain on the numerical rating scale (NRS) and physicians evaluated pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Pain assessed at baseline via the pain subscale of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C-30 (EORTC QLQ-C30) was significantly associated with C-reactive protein (CRP), a hepatic secretory protein associated with systemic inflammation ( 56 ). These findings were confirmed in a more recent study of 1,513 advanced cancer patients, which found patients in the highest quartile of CRP values had significantly increased pain compared to those in the lowest quartile ( 57 ). Moreover, another study identified high serum IL-6 concentrations in non-responders to the pain medication tramadol, which resulted in the use of stronger opioids in this group of patients ( 58 ).…”
Section: A Role For Pain In Cachexia Development and Progressionsupporting
confidence: 64%
See 1 more Smart Citation
“…Pain assessed at baseline via the pain subscale of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C-30 (EORTC QLQ-C30) was significantly associated with C-reactive protein (CRP), a hepatic secretory protein associated with systemic inflammation ( 56 ). These findings were confirmed in a more recent study of 1,513 advanced cancer patients, which found patients in the highest quartile of CRP values had significantly increased pain compared to those in the lowest quartile ( 57 ). Moreover, another study identified high serum IL-6 concentrations in non-responders to the pain medication tramadol, which resulted in the use of stronger opioids in this group of patients ( 58 ).…”
Section: A Role For Pain In Cachexia Development and Progressionsupporting
confidence: 64%
“…pain compared to those in the lowest quartile (57). Moreover, another study identified high serum IL-6 concentrations in nonresponders to the pain medication tramadol, which resulted in the use of stronger opioids in this group of patients (58).…”
Section: Figurementioning
confidence: 92%
“…The CNS is directly affected by inflammatory mediators in sickness, and the brain mediates cluster of behavioral changes (e.g., sleep disruption, cognitive impairment and memory deficits, disorientation, and reduction in motivated behavior) through communication systems between the immune system and the brain in humans and animals [20]. Other outcomes of sickness behavior, including weight loss (reduction of skeletal muscle mass and fat mass), increased catabolism (increased and lipolysis), circadian rhythm disorders (disarrangement eating habits and sleep-wake cycles), social disinterest, and sexual disinterest, appear to be a part of an integrated response of CNS and systemic inflammation , 5,6,19,20]. Accordingly, cancer cachexia has many overlapping features of sickness behavior.…”
Section: Rethinking Patient Experience Of Cancer Cachexia: Cancer Cac...mentioning
confidence: 99%
“…The CNS is directly affected by inflammatory mediators in sickness, and the brain mediates cluster of behavioral changes (e.g., sleep disruption, cognitive impairment and memory deficits, disorientation, and reduction in motivated behavior) through communication systems between the immune system and the brain in humans and animals [20]. Other outcomes of sickness behavior, including weight loss (reduction of skeletal 5,6,19,20]. Accordingly, cancer cachexia has many overlapping features of sickness behavior.…”
Section: Rethinking Patient Experience Of Cancer Cachexia: Cancer Cac...mentioning
confidence: 99%
See 1 more Smart Citation